Prevalence of factor V Leiden in patients with venous thrombosis - Cristiane Aparecida Michel; Julia B. Rocha; Daiane C. Costa; Carlos Augusto Lima; Anna Paula B. Batschauer
ABSTRACT INTRODUCTION: Venous thrombosis is a multifactor disease with high incidence in the population. The development of this disease is closely linked to the presence of environmental and genetic factors and may occur in combination or alone. Among the various genetic mutations that may predispose to a thrombotic event, the most frequent in the population is the G1691A mutation in clotting factor V, known as factor V Leiden (FVL). This mutation brings the phenotype known as activated protein C resistance, leading to a hypercoagulable state, which increases the risk of thrombosis. OBJECTIVE: To investigate the presence of FVL in individuals with history of venous thrombosis, and as the control group, individuals with no history of the disease. METHOD: The method used was the polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP). RESULTS: The results showed mutation prevalence of 21.5% in heterozygosity in patient group; no individuals with mutated homozygous were identified. The results also showed a high recurrence rate among the mutation carriers. CONCLUSION: In conclusion, the research of mutation on factor V has strong impact on investigation of venous thromboembolism, in order to elucidate the etiology of the event, and in treatment and in prophylaxis against the recurrence.